Loss of the Sigma Activity of RNA Polymerase of Bacillus subtilis during Sporulation - Linn, Thomas G. (1973)
The activity of the sigma subunit of the RNA polymerase of Bacillus subtilis decreases markedly during the first 2 hr of sporulation. Moreover, sigma activity remains deficient throughout the sporulation process and in dormant spores. The time course of changes in RNA polymerase during sporulation indicates that alterations in the core of RNA polymerase occur after the loss of sigma activity. Core RNA polymerase purified after the second and before the ninth hour of sporulation fails to respond to vegetative sigma subunit in vitro and contains variable amounts of a 110,000-dalton polypeptide in place of the β′ subunit. Core RNA polymerase purified from dormant spores has a subunit structure indistinguishable from vegetative core enzyme. RNA polymerase purified by antibody precipitation from an extract of a mixture of sporulating and excess vegetative cells separately labeled with two different radioisotopes contains β′ subunit and no 110,000-dalton polypeptide. However, RNA polymerase purified from sporulating bacteria in the absence of excess vegetative cells progressively loses the β′ subunit at each stage of purification even in the presence of the protease inhibitor, phenylmethyl sulfonyl fluoride. These findings suggest that the alteration of the β′ subunit is due to proteolysis in vitro.